2023
DOI: 10.1002/smll.202304585
|View full text |Cite
|
Sign up to set email alerts
|

Charge Storage Mechanism in Electrospun Spinel‐Structured High‐Entropy (Mn0.2Fe0.2Co0.2Ni0.2Zn0.2)3O4 Oxide Nanofibers as Anode Material for Li‐Ion Batteries

Abstract: High‐entropy oxides (HEOs) have emerged as promising anode materials for next‐generation lithium‐ion batteries (LIBs). Among them, spinel HEOs with vacant lattice sites allowing for lithium insertion and diffusion seem particularly attractive. In this work, electrospun oxygen‐deficient (Mn,Fe,Co,Ni,Zn) HEO nanofibers are produced under environmentally friendly calcination conditions and evaluated as anode active material in LIBs. A thorough investigation of the material properties and Li+ storage mechanism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…The HEO nanofibers present a granular architecture are comprised of densely packed oxide grains. Furthermore, they offer a narrow inner channel which is beneficial to Li + diffusion [69]. Triolo et al [122] have demonstrated that the morphologies of HEMs are influenced by the synthesis methods.…”
Section: The Influence Of Advanced Synthesis Methods On Hemsmentioning
confidence: 99%
“…The HEO nanofibers present a granular architecture are comprised of densely packed oxide grains. Furthermore, they offer a narrow inner channel which is beneficial to Li + diffusion [69]. Triolo et al [122] have demonstrated that the morphologies of HEMs are influenced by the synthesis methods.…”
Section: The Influence Of Advanced Synthesis Methods On Hemsmentioning
confidence: 99%
“…Currently, the preparation techniques of high-entropy oxides can be categorized according to the initial feedstock as well as the application. As shown in Figure 2, the preparation methods of HEOs include solid-state reaction method (high-temperature solid state reaction) [22,23], wet chemical methods (spray pyrolysis, co-precipitation, and solution combustion synthesis) [24][25][26][27][28][29][30], epitaxial growth of films (pulsed laser deposition and magnetron sputtering deposition) [31,32], and so on. This section focuses on the specific flow and characteristics of the process for the preparation of porous HEOs.…”
Section: Preparation Methods Of Porous Heosmentioning
confidence: 99%
“…In the same time, Cu becomes an inert element after initial lithiation. In chromium-free (MnFeCoNiZn) 3 O 4 , Santangelo et al 83 revealed that the reaction mechanism of Fe 3+ , Co 3+ /Co 2+ , and (Ni 3+ )/Ni 2+ is a single/multi-step redox behavior. Manganese is a partially reversible component with Mn 4+ /Mn 3+ present in the original HEOs and only Mn 3+ /Mn 2+ present after charge.…”
Section: Heos For Reversible Energy Storagementioning
confidence: 99%